Geochronological Constraint on the Evolution of the Aktyuz Terrane, Kyrgyz North Tianshan, and the Fate of the Taldybulak Levoberezhny Gold Deposit - Xi, Wei; Li, Nuo; Xia, Xiaohong; Ling, Xiaoxiao; Wu, Yanshuang (Frontiers in Earth Science, 2021)
The Aktyuz Terrane in Kyrgyz North Tianshan is of particular interest due to the occurrence of HP-UHP rocks as well as a giant gold deposit , i.e. Taldybulak Levoberezhny (abbreviated into Taldybulak Lev.). To constraint the ages of the host Kemin Complex and its auriferous monzogranite porphyry, detailed zircon U-Pb dating (by LA-ICPMS and SIMS) and Lu-Hf isotopic analyses were carried out. The intensively altered auriferous monzogranite porphyry yield two weighted mean average ages of 444 ± 3 Ma (n = 14, MSWD = 0.49, by LA-ICPMS) and 440 ± 5 Ma (n = 8, MSWD = 0.82, by SIMS) that are indistinguishable within error. Such ages are consistent with previous sulfide Re-Os isochron of 434  18 Ma (n = 6, MSWD = 24, Zhao et al., 2015, 2017), supporting a Silurian porphyry gold mineralization. The granitic gneiss yields a protolith age of 773  7 Ma (n = 7, MSWD = 0.04) and two metamorphic ages of 514  4 Ma (n = 8, MSWD = 0.09) and 483  3 Ma (n = 11, MSWD = 0.04). Detrital zircons from one fuchsite schist sample yield highly variable ages from 729  13 Ma to 2463  30 Ma, with 12 data weighted at 740  5 Ma (MSWD = 0.95). The metamorphic overgrowth yields a weighted mean average age of 460  4 Ma (n = 4, MSWD = 0.15). Detrital zircons in the migmatitic amphibolite are aged from 788  7 Ma to 3447  32 Ma, with two major concentrations at 941  7 Ma (n =13, MSWD = 0.95) and 794  5 Ma (n = 8, MSWD = 0.19). The metamorphic overgrowth yields an average age of 555  4 Ma (n = 8, MSWD = 0.65). The detrital and xenocryst zircons, as well as evolved εHf(t) values (−20.9 to −7.8) and old two stage Hf model ages (1367 to 3159 Ma), reveal the presence of Precambrian basement that may be dated back to Archean. The two metamorphic ages may correlate with the oceanic subduction and continental collision, respectively.